Development of Post Occupancy Evaluation Method for Climate Adaptive Building Shells: In Case of User Satisfaction Assessment of CABS - Hafizi, Nazgol (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2022)
Building development is one of the human activities with the greatest impact on sustainability. Many alternatives to address sustainability in architecture have been proposed in recent years and Climate Adaptive Building Shell (CABS) are one of the most promising solutions to date. CABS provide a response to this problem due to their adaptability and modifiability. Although CABS are promising solution for reducing energy consumption of the building, they have reputation for decreasing the occupant’s satisfaction. The examination of the CABS literature review using PRISMA methodology reveals that most of the research attention in this subject has been focused on economic and technological factors, while the occupant-centric study has been neglected. As a result, the fundamental purpose of this thesis is to conduct an occupant-centric study. The CABS literature and database were investigated in the first phase of this thesis. As a result, CABS office buildings were evaluated based on user-facade interaction types and scenarios to achieve the study's occupant-centric purpose. Finally, a new taxonomy for CABS office buildings that covers a wide range of topics was introduced. In the other hand, the literature review highlights the lack of research on occupants’ satisfaction, productivity and needs for this system. POE has traditionally been an effective approach for assessing user satisfaction. However, in its current state, this technique cannot fulfill the CABS's complexity and multi-domain properties. Thus, in second phase of study, after analyzing POE in general and identifying comfort characteristics, an attempt was made to design a unique POE model that can fulfill CABS requirements. As a result, a dynamic cloud-based POE was created within three main stages. In the first stage the model has been conceptualized with help of Human-Computer Interaction and Internet of Things Principles. The occupant-centered model tries to pinpoint the precise moment of discomfort. In the second stage, application of the model has been studied. For the Machine Learning of the model an active surrogate model with Artificial Neural Network architecture method has been applied. Lastly the relational data management system of the model has been studied. In last step the implementation of the model has been discussed. Finally, data assessment approaches for multi-criteria analysis and decision-making for CABS has been presented. The proposed model fills a gap in the literature of CABS studies linked to POE; nevertheless, due to a lack of recorded case studies on CABS, creating practical research on CABS for POE using proposed model is required.

ÖZ: Bina geliştirme, sürdürülebilirlik üzerinde en büyük etkiye sahip insan faaliyetlerinden biridir. Son yıllarda mimaride sürdürülebilirliği ele almak için birçok alternatif önerilmiştir ve iklim uyumlu bina kabuğu (CABS) bugüne kadarki en umut verici çözümlerden biridir. CABS, uyarlanabilirlikleri ve değiştirilebilirlikleri nedeniyle bu soruna bir yanıt sağlar. Her ne kadar CABS, binanın enerji tüketimini azaltmak için umut verici bir çözüm olsa da, bina kullanıcılarının memnuniyetini azaltma konusunda itibara sahiptir. CABS literatür taramasının PRISMA metodolojisi kullanılarak incelenmesi, bu konudaki araştırmaların çoğunun ekonomik ve teknolojik faktörlere odaklandığını, ancak kullanıcı merkezli çalışmanın ihmal edildiğini ortaya koymaktadır. Sonuç olarak, bu tezin temel amacı, kullanıcı merkezli bir çalışma yapmaktır. Bu araştırmanın ilk aşamasında CABS literatürü ve veri tabanı incelenmiştir. Sonuç olarak, CABS ofis binaları, çalışmanın kullanıcı merkezli amacına ulaşmak için kullanıcı-cephe etkileşim türleri ve senaryoları bazında değerlendirilmiştir. Son olarak, CABS ofis binaları için çok çeşitli konuları kapsayan yeni bir sınıflandırma tanıtılmıştır. Öte yandan, literatür taraması, bu sistem için bina kullanıcılarının memnuniyeti, üretkenliği ve ihtiyaçları konusunda araştırma eksikliğini vurgulamaktadır. Kullanım Sonrası Değerlendirme, geleneksel olarak kullanıcı memnuniyetini değerlendirmek için etkili bir yaklaşım olmuştur. Ancak, mevcut durumunda bu yaklaşım, CABS'nin karmaşıklığını ve çok alanlı özelliklerini yerine getiremez. Böylece çalışmanın ikinci aşamasında, genel olarak POE'nin analizi ve konfor özelliklerinin belirlenmesinden sonra, CABS gereksinimlerini karşılayabilecek benzersiz bir POE modeli tasarlanmaya çalışılmıştır. Sonuç olarak, üç ana aşamada dinamik bir bulut tabanlı POE oluşturuldu. İlk aşamada model, İnsan-Bilgisayar Etkileşimi ve Nesnelerin İnterneti İlkeleri yardımıyla kavramsallaştırılmıştır. Kullanıcı merkezli model, tam olarak rahatsızlık anını belirlemeye çalışmıştır. İkinci aşamada ise modelin uygulaması incelenmiştir. Modelin yapay öğrenmesi için Yapay Sinir Ağı mimarisi yöntemi ile aktif bir vekil model uygulanmıştır. Son olarak modelin ilişkisel veri yönetim sistemi incelenmiştir. Son aşamada ise modelin uygulanması tartışılmıştır. Son olarak, CABS için çok kriterli analiz ve karar verme için veri değerlendirme yaklaşımları sunulmuştur. Önerilen model, POE ile bağlantılı CABS çalışmaları literatüründeki bir boşluğu doldurmaktadır; yine de, CABS üzerine kaydedilmiş vaka çalışmalarının olmaması nedeniyle, önerilen modeli kullanarak POE için CABS üzerine pratik araştırmaların oluşturulması gerekmektedir.
Doctor of Philosophy in Architecture. Institute of Graduate Studies and Research. Thesis (Ph.D.) - Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2022. Supervisor: Prof. Dr. Sadiye Müjdem Vural.
Keywords: Architecture Department; Sustainable buildings--Climate Adaptive Building Shells--Design and construction; Sustainable Buildings--Energy Consrvation--Energy Consumption; CABS, POE, User-Centric Design, Dynamic-Cloud modelling, HCI, ML; Buildings--Environmental Engineering; Buildings--Thermal Properties; Architecture and Climate; Buildings--Energy Conservation